Astrology, modernity and the project of self-identity. Issue 3 (2nd July 2020) - Clements, Paul
ABSTRACT: This speculative and interdisciplinary article about Western and UK astrology recognises a fluid craft steeped in pre-modern 'magical' symbolism accommodating to differing degrees the modern, linear and literal. It embraces an open framework and employs personal experience that highlights the problems with self-understanding. Astrology may appear detached from its traditional religious foundation and has struggled for cultural legitimacy, but it offers a spiritual understanding, self-knowledge and self-determination. It divines a range of symbolic possibilities that encourages elective biography and instructs the project of self-identity. This in part assuages the existential need to find meaning, questioning established thinking and 'rational' cultural practices. Astrology embeds a spiritual outlook that co-exists with profane individualism and materiality highlighting dissonant modernity.